2020
DOI: 10.1101/2020.03.11.987586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Erythropoietin production by the kidney and the liver in response to severe hypoxia evaluated by Western blotting with deglycosylation

Abstract: 31The detection of erythropoietin (Epo) protein by Western blotting has required pre-purification 32 of the sample. We developed a new Western blot method to detect plasma and urinary Epo using 33 deglycosylation. Epo in urine and tissue and erythropoiesis-stimulating agents (ESAs) in urine 34 were directly detected by our Western blotting. Plasma Epo and ESAs were detected by our 35 Western blotting after deglycosylation. The broad bands of Epo and ESAs were shifted to 22 36 kDa by deglycosylation except PEG-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…We cut the 22 kDa band of deglycosylated Epo isolated from an anemic patient's urine and analyzed it by LC/MS. We found that the band contained human Epo, proving the correctness of our method 13 . Using this method, we compared endogenous Epo and exogenous ESAs.…”
Section: Main Textsupporting
confidence: 57%
See 3 more Smart Citations
“…We cut the 22 kDa band of deglycosylated Epo isolated from an anemic patient's urine and analyzed it by LC/MS. We found that the band contained human Epo, proving the correctness of our method 13 . Using this method, we compared endogenous Epo and exogenous ESAs.…”
Section: Main Textsupporting
confidence: 57%
“…LC/MS analysis detected endogenous rhEpo and exogenous ESAs both in glycosylated and deglycosylated forms as deglycosylated Epo of 22 kDa (Suppl Table 1). We have shown that endogenous Epo is detected as a 22 kDa band in our previous report 13 . Our data clearly show that LC/MS analysis cannot differentiate endogenous rhEpo and exogenous ESAs since LC/MS analysis needs trypsin digestion of samples 14 .…”
Section: Main Textmentioning
confidence: 52%
See 2 more Smart Citations